Life-Cycle Cost Analysis to Evaluate Infrastructure Pavement Design in Western Australia - Whyte, Andrew; Pham, Anna (University Teknologi PETRONAS, 2012)
Decision-support tools and asset management throughout the life-cycle and at the planning phase of civil infrastructure projects are essential for stakeholders charged with the determination of cost-effective design-solutions over the useful life of an asset. The need for a LCCA (life-cycle cost analysis) to guide economic decision-making when comparing competing alternatives is explored by project review of actual specification alternatives towards a case-study that contrasts the pavement design options of: concrete; and, asphalt. Clear cost foundations are applicable. Cost factors were obtained from actual live valid experience predominately. Discussion is made of the processes involved in developing a LCCA model for infrastructure with consideration of options; namely direct whole-life cost comparison of: thin asphalt surfaced unbound granular pavement (AC); and, continually reinforced concrete pavement (CRCP). Life-cycle periods of 100, 60 and 30 years, with an 8% discount rate (incorporating sensitivity analyses), results indicate that a pavement alternative of asphalt is least cost in all cases. This project vindicates and validates the need for a LCCA for civil engineering pavement, and specifically recommends that asphalt is a less expensive infrastructure alternative than concrete in Western Australia.